Severe dopaminergic neuron loss in rhesus monkey brain impairs morphine-induced conditioned place preference - Yan, Ting; Rizak, Joshua Dominic; Wang, Jianhong; Yang, Shangchuan; Ma, Yuanye; Hu, Xintian (Frontiers in Behavioral Neuroscience, 2015)
It is well known that dopamine is critical for reward, but the precise role of dopamine in reward remains uncertain. The aim of this study was to determine what percentage of dopaminergic neurons in the primate brain is required for the expression of conditioned reward by measuring the performance of dopamine-deficient rhesus monkeys in a morphine-induced conditioned place preference paradigm. Animals with mild Parkinsonian symptoms successfully developed and retained a morphine preference that was equivalent to control monkeys. However, these monkeys could not maintain the preference as well as controls when they retained severe Parkinsonian symptoms. On the other hand, monkeys initially in a severe Parkinsonian state developed a preference for morphine, but this preference was weaker than that of the controls. Histological results showed that the loss of dopaminergic neurons in monkeys that had severe Parkinsonian symptoms was about 80% in comparison to the control monkeys. All these data suggest that a severely impaired dopamine system alters rewarding-seeking behavior in non-human primates.